The Symbiotic Fungus Leucoagaricus gongylophorus (Möller) Singer (Agaricales, Agaricaceae) as a Target Organism to Control Leaf-Cutting Ants - Araújo, Sean (2022)
Atta and Acromyrmex are the main genera of leaf-cutting ants present in North and South America, causing extensive damage to agroforestry. Control of the ants requires high handling costs with few effective methods available to decrease the losses. The symbiosis between the leaf-cutting ants and the fungus Leucoagaricus gongylophorus is essential for ant nest survival. Therefore, L. gongylophorus may be a key target in controlling leaf-cutting ants, since its reduction may cause an imbalance in the symbiosis necessary to maintain the nest. Among the options for natural fungal control, plant species are considered important sources of compounds belonging to several classes of natural products that show potential as antifungal agents. This review also presents studies that establish that the antagonist fungi from the Escovopsis and Trichoderma genera effectively reduce the development of L. gongylophorus. The development of nanostructured delivery systems, which have shown advantages over conventional formulations, is suggested for ant control; no commercial nanotechnology-based product has yet been developed, and this appears to be a new approach for future studies.